Quantum dot light-emitting diode with quantum dots inside the hole transporting layers - Leck, Kheng Swee (2013)
We report a hybrid, quantum dot (QD)-based, organic light-emitting diode architecture using a noninverted structure with the QDs sandwiched between hole transporting layers (HTLs) outperforming the reference device structure implemented in conventional noninverted architecture by over five folds and suppressing the blue emission that is otherwise observed in the conventional structure because of the excess electrons leaking towards the HTL. It is predicted in the new device structure that 97.44% of the exciton formation takes place in the QD layer, while 2.56% of the excitons form in the HTL. It is found that the enhancement in the external quantum efficiency is mainly due to the stronger confinement of exciton formation to the QDs.